2014
DOI: 10.1084/jem.20141132
|View full text |Cite
|
Sign up to set email alerts
|

Control of lymphocyte egress from lymph nodes through β2-adrenergic receptors

Abstract: Using pharmacological activation and genetic ablation of β2-adrenergic receptors (β2ARs) in mice, Nakai et al. show that β2ARs expressed on lymphocytes can regulate egress of these cells from lymph nodes, while altering the responsiveness of chemokine receptors CCR7 and CXCR4. They identify that β2ARs can physically interact with these chemokine receptors. And, in mouse models of T cell–mediated inflammation, β2AR-mediated signals are shown to inhibit trafficking of antigen-primed T cells, reducing their numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
215
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(234 citation statements)
references
References 51 publications
11
215
2
Order By: Relevance
“…Such molecules are for example CCL12 and CCL19. On the other hand, there are some unexpected candidates such as for example the β2-adrenergic receptor that has been recently described as an important receptor on lymphocytes regulating lymphocyte egress from LNs by enhancing retention-promoting signals through CCR7 and CXCR4 (23). Preferential expression of the β2-adrenergic receptor on the lymphatic endothelium of the SS in our analyses suggests that it may also have a role in the lymphatics.…”
Section: Discussionmentioning
confidence: 67%
“…Such molecules are for example CCL12 and CCL19. On the other hand, there are some unexpected candidates such as for example the β2-adrenergic receptor that has been recently described as an important receptor on lymphocytes regulating lymphocyte egress from LNs by enhancing retention-promoting signals through CCR7 and CXCR4 (23). Preferential expression of the β2-adrenergic receptor on the lymphatic endothelium of the SS in our analyses suggests that it may also have a role in the lymphatics.…”
Section: Discussionmentioning
confidence: 67%
“…A recent study showed that activation of the β2 adrenergic receptor (β2AR) inhibited egress of naive CD4 and B cells and of effector OTII cells from the LN (33). This retention was mediated by an interaction of β2AR with CCR7 and CXCR4.…”
Section: Discussionmentioning
confidence: 99%
“…However, only CCR2 deficiency had a negative effect on BM cell migration in response to its ligand CCL2. This was in the absence of deficiencies in egress of cells from BM (7) that occur with global depletion of CCR2 (17,18). Although the importance of CCL2 as a major chemoattractant of mononuclear cells to the ischemic heart has been extensively studied, the results are often in conflict, with both administration and inhibition of CCL2 showing improvements and detrimental effects in the remodeling following MI (19,20).…”
Section: Discussionmentioning
confidence: 99%